Optimizing Design of Core-clad Width for Single Mode Fiber with Zero Dispersion Shift - Toto Saktioto; Doni Basdyo; Yoli Zairmi; Romi Fadli Syahputra; Okfalisa Okfalisa; Wresni Anggraini; Syamsudhuha Syamsudhuha (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Fiber optics have become a vital role in telecommunication technologies with many benefits, i.g. high speed transmission, non-electromagnetic interference and low energy consumption. An excellent single mode fiber (SMF) must provide a low attenuation and dispersion which occurs at same wavelength, i.e. 1550 nm. But, in silica based SMF, this property cannot be achieved in a bulk form. Meanwhile, the direct experiment is really not the best choice. Therefore, a simulation fiber design take a crucial role into account for obtaining zero dispersion shift. We design SMF geometry with zero dispersion by resizing the width of core and cladding. This design consists of inner and outer core-clad profile. We also provide several width boundaries for matching the lowest dispersion to the lowest attenuation in silica fiber-based. Moreover, the results shows that dispersion property of the design is suitable for long-haul optical communication systems.